2022
DOI: 10.3390/rs14184660
|View full text |Cite
|
Sign up to set email alerts
|

Winter Wheat SPAD Value Inversion Based on Multiple Pretreatment Methods

Abstract: SPAD value was measured by a portable chlorophyll instrument, which can reflect the relative chlorophyll content of vegetation well. Chlorophyll is an important organic chemical substance in plants that acquires and transmits energy during photosynthesis. The continuous spectral curve of winter wheat can be obtained rapidly in a specific band range by using hyperspectral remote sensing technology to estimate the SPAD value of winter wheat, which is of great significance to the growth monitoring and yield estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…FD reflects the slope of the spectrum, while SD represents the change in the slope of the reflection spectrum. While SD identifies more absorption peaks, it also introduces noise and may result in errors ( Shen et al., 2022 ). Therefore, FD is strongly correlated with AGB and can be effectively utilized for estimating rice AGB.…”
Section: Discussionmentioning
confidence: 99%
“…FD reflects the slope of the spectrum, while SD represents the change in the slope of the reflection spectrum. While SD identifies more absorption peaks, it also introduces noise and may result in errors ( Shen et al., 2022 ). Therefore, FD is strongly correlated with AGB and can be effectively utilized for estimating rice AGB.…”
Section: Discussionmentioning
confidence: 99%
“…This further proves that, if only the correlation analysis method is used to select the characteristic bands, some characteristic values will be ignored. Wavelet packet, as an effective method to remove noise during signal processing, has been used by many other scholars for the preprocessing of soil spectra [63,64]. The Shannon entropy wavelet packet transformation can solve the problem that the wavelet coefficients need to be artificially selected multiple times in the pruning judgment of the wavelet packet transformation.…”
Section: Pso-lssvr Modelingmentioning
confidence: 99%
“…This study offers valuable research support for future predictions of maize SPAD. In the study from Shen Lanzhi et al [21], they performed preprocessing on hyperspectral data using a combination of wavelet packet denoising, first-order derivative transformation, and principal component analysis. The results indicated that this preprocessing approach enhanced the accuracy and stability of the PLSR model.…”
Section: Introductionmentioning
confidence: 99%